Development of proline-based chiral ionic liquid organocatalyst for asymmetric Michael reaction under microwave irradiation - Omar, Emmy Maryati (2013)
Recent developments in organocatalysis have shown that chiral ionic liquid organocatalysts can be advantageously performed in various organic solvents and ionic liquids. Along with the good catalytic performance especially in Michael reaction, some drawbacks such as high catalyst loading, large excess of substrates and long reaction time need to be improved in the reaction processes. In this thesis, four aspects of the title objectives were studied. In the first part, eight proline derived amino acids were successfully screened for good catalytic activity and selectivity towards Michael products. L-proline amino acid has been identified as the most active organocatalyst and selective small organic molecule in the Michael reaction of aldehydes to nitrostyrenes. A high percentage yield (> 92%), moderate enantioselectivity (28% ee) and high diastereomeric ratio (90/10) were obtained using 30 mol% catalyst loading, 2 aldehyde equivalent ratio and 9 hours reaction time in isopropanol solvent at room temperature. Beside organic solvent, the uses of environmentally-friendly ionic liquids were explored. The 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([Bmim][NTf2]) ionic liquid was found to be the best solvent media compared to other ten more ionic liquids. The results obtained with high percentage yield (90%), slightly increased in enantioselectivity (38% ee) and high diastereomeric ratio (91/9). In order to develop the catalytic activity, microwave irradiation technique was used to shorten the Michael reaction time. The time was successfully reduced from 8-9 hours to 5-40 min at temperature 60 oC with almost similar results as in room temperature and conventional heating conditions. The [Bmim][NTf2] ionic liquid was reused five times, representing an economic alternative to conventional organic solvents. The synthetic reaction was optimized by Response Surface Methodology (RSM) approach. Design of experiments based on Central Composite Design (CCD) was used to evaluate the interactive effects of the reaction parameters including catalyst loading, substrate equivalent ratio and reaction time. By RSM optimization, a catalyst loading could be reduced from 30 to 10 mol% with high percentage yield (97%) and moderate enantioselectivity (37% ee). Large excess of aldehyde (normally 10-20 equiv ratio) that has been used in organocatalysis field was also successfully reduced to 2 equivalent ratio indicating that the RSM approach can be applied effectively to optimize the Michael reaction of aldehyde to ß-nitrostyrene. The proline-based chiral ionic liquid (CIL) organocatalysts were designed and synthesized in order to overcome some of the drawbacks by L-proline. These chiral ionic liquids contain a chiral pyrrolidine (proline-based) backbone and incorporated with ionic species. Without any additive, the reaction of CIL imidazolium (S)-pyrrolidine sulfonamide organocatalyst was found to be very effective in isopropanol at room temperature in giving excellent yields (up to 90%), shorten time constraint (3-5 hours), and high diastereoselectivities (95/5). The results also demonstrated that [Bmim][NTf2] ionic liquid was not suitable solvent as it reduced the catalytic activity not only at room temperature but also under microwave irradiation. However, the reaction of CIL imidazolium (S)-pyrrolidine sulfonamide organocatalyst was found to be effective under microwave irradiation in isopropanol with very high yield (99%) with slightly increased in enantioselectivity (42% ee) in 10 min reaction time. The understanding of the stereoselectivity on the mechanism catalyzed by CIL imidazolium (S)-pyrrolidine sulfonamide organocatalyst was also investigated by General Atomic and Molecular Electronic Structure System (winGAMESS) software in the last part of the thesis. This approach indicated that the N−H acidic hydrogen from the CIL imidazolium (S)-pyrrolidine sulfonamide organocatalyst plays an important role in the reaction by forming a hydrogen bond to the nitrostyrene substrate that leads to C−C bond formation by the enamine mechanism. The computational results agree quite well with the observed stereoselectivity of chiral ionic liquid organocatalyst for the Michael reaction of aldehyde to nitrostyrene.